Effects of Age and Height on Selected Properties of Three Malaysian Bamboo Species - Mohmod, Abdul Latif (1991)
Although bamboo is widely found in Peninsular Malaysia , little research has been conducted on its importance for industrial use. A study was initiated to evaluate the effect of age and height of three common bamboo species namely Bambusa blumeana Schult. 'Buluh duri', Bambusa vulgaris Schrad. 'Buluh minyak' and Gigantochloa scortechinii Gamble 'Buluh semantan' on their anatomical, physical, mechanical and machining properties and durability against borers. All the anatomical properties except radial / tangential ratio of the vascular bundles size, showed no significant relationship with age and height. The fibres of both the Bambus a species were shorter than those of G. scortechinii (ranges of 1.74 - 3.76 mm and 3.50 - 4.24 mm, respectively). The average cell wall thickness of the three bamboo species was in the range of 5 - 7 µm.